Legality of the currency clause after entry into force of the Law on Conversion - Radović Mirjana (Anali Pravnog Fakulteta u Beogradu)
This paper deals with legality of the currency clause in light of the Law on Conversion of Housing Loans Indexed in Swiss Francs. The first part analyses characteristics of the currency clause, in order to explain effects of its possible illegality on validity of the loan agreement. The author emphasizes inconsistency in the way Serbian courts approach this issue and suggests arguments for treating the loan agreement as being only partially invalid. The second part presents different opinions regarding legality of the Swiss francs currency clause, which is generally treated as an invalid contract term in judicial practice. Thereafter, solutions to the problem of Swiss francs in the Law are examined. It is concluded that conversion is not possible if the original loan agreement was invalid due to an illegal currency clause. Consequently, illegality of the currency clause remains open after entry into force of the said Law.